An Investigation Of Liposomes For Oral Delivery Of A Poorly Bioavailable Model Drug: Griseofulvin - Ong , Sandy Gim Ming (2011)

(untitled)
The potential of liposomal formulation as a drug delivery system for oral administration of poorly bioavailable drugs was studied using griseofulvin as the model drug. An extrusion technique using a self-assembled instrument was evaluated for nanosizing the liposomes. The particle size and size distribution of liposomes produced was affected by various processing parameters. Nevertheless, the extrusion method was simple, reproducible and more effective compared to other size-reduction methods evaluated.